2021
DOI: 10.1037/rel0000177
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects from aspects of religion on female genital mutilation/cutting.

Abstract: Religion has been seen as one of the most important predictors of female genital mutilation/cutting (FGM/C), yet there are almost no studies that empirically examine how religion affects the parents’ decision to subject their daughters to FGM/C. Thus, the authors investigated how several aspects of religiosity—religious affiliation, prayer frequency, religious service attendance, religious fundamentalism, perceived governmental unfairness toward one’s own religious group, and perceived religious suppression—co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
(45 reference statements)
0
9
0
3
Order By: Relevance
“…In accordance with terror management theory (Greenberg, Pyszczynski, & Solomon, 1986), religious fundamentalist beliefs might protect people from uncertainty and existential fear; however, when the fundamentalist worldview is challenged, people, who would not normally condone violence, might be prone to support honor violence to mitigate these threats to their worldview. Empirically, several studies suggested that religious fundamentalism might indeed be associated with increased violent attitudes (e.g., Beller, 2017; Beller & Kröger, 2018a; Beller, Kröger, & Kliem, 2021; McCleary, Quillivan, Foster, & Williams, 2011). For example, Williamson and Hood (2014) confronted participants with three scenarios that presented varied threats to the participants’ worldviews.…”
Section: Religion As a Predictor Of Honor Violencementioning
confidence: 99%
“…In accordance with terror management theory (Greenberg, Pyszczynski, & Solomon, 1986), religious fundamentalist beliefs might protect people from uncertainty and existential fear; however, when the fundamentalist worldview is challenged, people, who would not normally condone violence, might be prone to support honor violence to mitigate these threats to their worldview. Empirically, several studies suggested that religious fundamentalism might indeed be associated with increased violent attitudes (e.g., Beller, 2017; Beller & Kröger, 2018a; Beller, Kröger, & Kliem, 2021; McCleary, Quillivan, Foster, & Williams, 2011). For example, Williamson and Hood (2014) confronted participants with three scenarios that presented varied threats to the participants’ worldviews.…”
Section: Religion As a Predictor Of Honor Violencementioning
confidence: 99%
“…On the other hand, the current investigation is one of the few studies that have adequately operationalized religiosity as a multidimensional phenomenon (Glock, 1962). Evidence is mounting that religiosity is a complex multidimensional construct with differential associations to violence (e.g., Beller & Kröger, 2018; Beller, Kröger, & Kliem, 2019), supporting the choice of operationalization used in this study.…”
Section: Discussionmentioning
confidence: 72%
“…Wenn auch die Religionen keine Beschneidung fordern und kulturelle Bedingungen der Herkunftsländer großen Einfluss besitzen [24], haben doch 21,6 % der Befragten angegeben, dass die Beschneidung durch ihre Religion gefordert würde. Trotz langjähriger Bemühung der WHO, des Kinderhilfswerk der Vereinten Nationen (UNICEF), Terre de Femme (TdF) und anderer internationalen Institutionen hat die Aufklärung über die gesundheitlichen Folgen, noch immer nicht zu einem ausreichenden Umdenken geführt.…”
Section: Fortsetzungunclassified
“…Die Hoffnung ist dennoch, dass Aufklärung bei afrikanischen Eltern dazu führt, dass es sozial akzeptierter wird, ihre Töchter nicht beschneiden zu lassen. Somit könnte das Auftreten in der nächsten Generation vermindert werden [24]. Dieses Dokument wurde zum persönlichen Gebrauch heruntergeladen.…”
Section: Fortsetzungunclassified